Potensi Bunga Telang Sebagai Antioksidan dalam Produk Olahan Seduhan Teh Herbal - Puspita Dewi, niluh; Maramis (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The telang flower plant is known as the Latin Buterfly pea, while the scientific language is Clitoria ternatea. Telang (Clitoria ternatea) is a type of wild plant that has health benefits for the human body. One of the processed pea flower that is useful is as a health drink. The potential of the telang flower has been proven through several studies, namely the bioactive components found in the telang flower, including flavonol glycosides, anthocyanins, flavones, flavonols, phenolic acids, terpenoid and alkaloid compounds, as well as cyclic peptide compounds or cyclotides. This community service activity aims to provide education to residents of Sopu Village, Nokilalaki District, Sigi Regency about the benefits of telang flower and can use it into processed products, such as fresh and dried herbal tea of ​​telang flower. The implementation method of this community service activity is the lecture, discussion and question and answer method. The results of this counseling, it is hoped that the residents of Sopu Village, Nokilalaki District, Sigi Regency have an independent business in making products made from telang flower so that they can improve the economy of the residents of Sopu Village.